Peran Media Sosial Instagram dalam Pembentukan Kepribadian Gen Z Kecamatan Sumbersari Kabupaten Jember - Jane Sabathani Putri; Rizaldy Andy Wijaya; Vanessa Marcia Hitipeuw (TUTURAN: Jurnal Ilmu Komunikasi, Sosial dan Humaniora, 2023)
Technological advances, unfortunately, are currently developing, which have a significant impact on all humans in this world. Changes in people's lifestyles that are currently being felt in everyday life have made people aware that technology and the internet are quite a significant influence on them. The emergence of the internet is enough to minimize difficulties and provide convenience for something you want to do. The use of the internet, which is dominated by Gen Z, actually brings about cultural changes, even the lifestyle of teenagers around the Sumbersari sub-district, Jember Regency. Thus, as time goes by, there are many interactions that develop from the community itself, such as patterns of communicating in the network, the development of digital businesses carried out by young men and women. The development of the times is increasingly making everything easier to reach.